2019
DOI: 10.1038/s41598-018-38376-8
|View full text |Cite
|
Sign up to set email alerts
|

Functional expression of the mechanosensitive PIEZO1 channel in primary endometrial epithelial cells and endometrial organoids

Abstract: Successful pregnancy requires the establishment of a complex dialogue between the implanting embryo and the endometrium. Knowledge regarding molecular candidates involved in this early communication process is inadequate due to limited access to primary human endometrial epithelial cells (EEC). Since pseudo-pregnancy in rodents can be induced by mechanical scratching of an appropriately primed uterus, this study aimed to investigate the expression of mechanosensitive ion channels in EEC. Poking of EEC provoked… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
36
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 60 publications
4
36
0
Order By: Relevance
“…By exposure to a specific hormone treatment protocol encompassing E2 and progesterone (P4), organoids mimicked the full menstrual cycle as well as incipient decidualization (Table 1 and Supplementary Table 3). The robustness of the endometrial organoid platform has been validated by IHC, electron microscopy, array Comparative Genomic Hybridization (aCGH) and transcriptome analysis and, in addition, ion channel functionality and ciliogenesis was demonstrated using these organoid systems (Fitzgerald et al, 2019;Haider et al, 2019;Hennes et al, 2019;Cochrane et al, 2020;Bui et al, 2020;Luddi et al, 2020;Syed et al, 2020). Two groups achieved to derive organoids from trophoblasts, offering the appealing possibility to study trophoblast-endometrium crosstalk in vitro (Haider et al, 2018;Turco et al, 2018).…”
Section: Endometrium Healthy Endometriummentioning
confidence: 99%
“…By exposure to a specific hormone treatment protocol encompassing E2 and progesterone (P4), organoids mimicked the full menstrual cycle as well as incipient decidualization (Table 1 and Supplementary Table 3). The robustness of the endometrial organoid platform has been validated by IHC, electron microscopy, array Comparative Genomic Hybridization (aCGH) and transcriptome analysis and, in addition, ion channel functionality and ciliogenesis was demonstrated using these organoid systems (Fitzgerald et al, 2019;Haider et al, 2019;Hennes et al, 2019;Cochrane et al, 2020;Bui et al, 2020;Luddi et al, 2020;Syed et al, 2020). Two groups achieved to derive organoids from trophoblasts, offering the appealing possibility to study trophoblast-endometrium crosstalk in vitro (Haider et al, 2018;Turco et al, 2018).…”
Section: Endometrium Healthy Endometriummentioning
confidence: 99%
“…Similarly to the organoids from the fallopian tube, inhibition of NOTCH signaling is involved in ciliogenesis that is dependent on the presence of estrogen [79]. As an example of how the organoids can be used to study endometrial physiology, the role of the mechanosensitive ion channel PIEZO1 was investigated and shown to be involved in the establishment of a dialogue at the maternal-fetal interface that could act as a potential target for promoting successful implantation [83].…”
Section: Endometriummentioning
confidence: 99%
“…The molecular mechanisms of mechanosensing and mechanotransduction include factors such as the Hippo pathway effector Yap (Lian et al, 2010;Dupont et al, 2011;Benham-Pyle et al, 2015) as well as the mechanically gated ion channels Piezo1/2 (Pathak et al, 2014;Hennes et al, 2019), which produce their effects either indirectly, e.g., through Yap nuclear translocation, or directly, e.g., through the nucleocytoskeleton and cytoskeleton (LINC) complex (Stewart et al, 2015). Indeed, Yap changes its localization from cytoplasmic (no mechanical stimulation/inactive form) to nuclear (under mechanical stimulation/active form) (Dupont et al, 2011) and Yap has been shown to play an important role in stem cell differentiation, with its levels gradually decreasing during the transition from pluripotency (Lian et al, 2010).…”
Section: Role Of Mechanical Cues In Developing Tissuesmentioning
confidence: 99%
“…Piezo1 has notably also been involved in determining lineage choice in human neural stem cells, where activation by traction forces resulted in neurogenesis, while inhibition gave rise to astrocytes and limited neuronal differentiation (Pathak et al, 2014). Another study in human endometrial epithelial cells (hEECs) demonstrated that activation of Piezo1 was a direct response to cell membrane mechanical indentation, suggesting such mechanoregulation may be important in embryo implantation (Hennes et al, 2019). Interestingly, endometrial organoids were used here as a model system which could sustain longer culture under mechanical activation compared to primary hEECs.…”
Section: Role Of Mechanical Cues In Developing Tissuesmentioning
confidence: 99%